Situação da leishimaniose visceral em um município endêmico do Estado do Maranhão - Lago, Rafiza de Josiane Mendes do (2014)
Among the clinical forms of leishmaniasis, the visceral leishmaniasis (VL) or kala-azar constitutes the most severe, with high levels of lethality. This study aimed to assess the situation of visceral leishmaniasis in an endemic municipality in the state of Maranhão, through a descriptive study conducted from November 2012 to November 2014. The study included 80 cases of VL reported in the city during the period 2008-2012, and 273 families in the area with the highest number of cases of VL. Control actions performed by the municipality were obtained from documentary records and interviews with officials. It was found that 97.50% cases were autochthonous and 66.30% coming from the urban area. Men (61.25%), age 5 to 9 years (43.75%), mixed race (82.50%) and people with little or no schooling (61.25%) were the most affected. The most widely used method for diagnosis was IFI (70%), and pentavalent antimony was the most used drug for treatment (93.75%). Among the reported cases, 67.50% were discharged as cured. In relation to socio-demographic and environmental characteristics of families, the majority of residences was made of bricks (82.40%) and covered with tile (96.70%). Houses had four to six people (53.80%) who living below minimum wage (53.50%) income. Services of water supply (99.30%), garbage collection (79.50%) and the presence of septic tank was reported by 68.13% of respondents. Animal husbandry (57.14%) and the presence of those animals near the home (84.25%) was mentioned. Favorable conditions for the maintenance of VL vector were cited by 25.73% of residents. VL cases were mentioned in the family (10.26%) and neighborhood (30.04%). Respondents were unaware of performing control actions to the reservoir and vector of VL in the city (93.64%). Among families with a history of VL, 56.25% reported that they were not followed during treatment. Representatives of the city describe management strategies for VL focused on early diagnosis and treatment of cases, reducing the population of sandflies, elimination of reservoirs and health education activities. Conclusion: Visceral leishmaniasis is an important public health problem in Itapecuru Mirim, with cases reported in all age groups, both sexes, in people with low education and living in the urban area of the city. Most cases resulted in cure. Observed housing conditions do not reflect the expected standard for VL, but the locals refer cases of the disease in the family and also in the neighborhood. Control strategies for VL were described in the municipality. However, such actions occur sporadically.